(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: The study aimed to survey the physical activity status of students majoring in nutrition and public health and some related factors. Subjects and methods: A cross-sectional study was conducted on students majoring in nutrition and public health at Pham Ngoc Thach University of Medicine. Results: Our sample size was 349 students. The percentage of students who meet the WHO recommendation on physical activity (PA) is 41.8%. There is a statistically relationship between PA and gender, year of study and nutritional status. Conclusion: The prevalence of students meeting the WHO recommendation on PA is not high and it is neccessary to propose some approach to improve this situation. Related factors are gender, year of study and nutritional status.